Sosialisasi dan Edukasi Pencegahan Tindak Kekerasan Seksual di Lingkungan Sekolah - Muhammad Tahir; Abunawas Abunawas (Journal of Community Development, 2024)
Sexual violence in the school environment will increase throughout 2021-2023. Most incidents of harassment occur in junior high schools (SMP). This community service activity (PKM) aims to socialize and educate students in the SMPN 8 Sungai Kakap school environment regarding the prevention of sexual violence, so as to reduce the incidence of these cases. This activity is carried out using the educational lecture method accompanied by watching educational videos. This PKM activity was attended by 35 people consisting of students, several school teachers and student teams assigned to the school in the Teaching Campus 7 (KM7) program. Evaluation of the activity in the form of filling out a questionnaire was carried out before the activity (pre test) and after the activity was completed (post test) to participants regarding the educational material for preventing acts of sexual violence delivered by the implementing team. The results of the evaluation showed that the participants' understanding abilities were better than before, or had increased.